Transformasi Tempat Penampungan Sampah Konvensional Menjadi TPS3R di Desa Bungurasih Kabupaten Sidoarjo - Tri Sunan Agung; Syahfa Adinda Relyando (Universitas Andalas, 2026)
The increasing volume of waste generation in Bungurasih Village, Sidoarjo Regency, has created an urgent need for adequate waste management facilities. The existing Temporary Waste Storage (TPS) is suboptimal, equipped only with four simple transport carts and an incinerator lacking an emission control system. This study aims to evaluate the current condition of the TPS, analyze waste composition, density, and generation rate, and redesign the facility into a Reduce, Reuse, Recycle Waste Processing Site (TPS3R). The research employed a literature review and qualitative descriptive approach, supported by primary data collection through eight consecutive days of sampling. The results indicate that the average waste density reaches 428.84 kg/m³, with a daily waste generation of 6,359.70 kg. The redesign includes the construction of a TPS3R on an area of 809 m², consisting of sorting zones, organic waste processing, composting, storage, and supporting facilities. The estimated total cost for the TPS3R construction is IDR 1,769,480,000. This result is expected to serve as a planning reference for community-based integrated waste management systems in rural areas.